Exploring the potential of micro-credentials: A systematic literature review - Tamoliune, Giedre; Greenspon, Rasa; Tereseviciene, Margarita; Volungeviciene, Airina; Trepule, Elena; Dauksiene, Estela (Frontiers in Education, 2023)
Micro-credentials have recently become a huge research interest, as they play an important role in the social, economic, and higher education sectors. Mindful of growing critique in some circles and recent publications, this paper offers an informed analysis of the potential of micro-credentials to foster post-COVID-19 pandemic recovery across a spectrum of dimensions, including supporting innovation in higher education institutions (HEIs). It reports a systematic literature review analysis of scientific articles published between 2015 and January 2022 on micro-credential research in the field of higher education. Results of a bibliometric and qualitative content analysis from 32 scientific articles provided insights into the potential of micro-credentials to foster post-pandemic recovery through social, economic, and higher education innovations. The findings suggest that the potential can be unfolded through multiple dimensions, like offering more possibilities for individuals to up-skill, re-skill and enter the labor market (economic context), enhancing lifelong learning by developing flexible personal learning pathways (social context), extending services in assessment and recognition of non-formal and informal learning, and introducing stackable credits and previous qualifications (higher education context). Even though the paper analyses scientific articles from the pre-pandemic and pandemic period, this study aim to systematize the results of other researchers and to offer sound insights into how further development in micro-credentials could contribute to the post-pandemic recovery.